2023
DOI: 10.3390/ijms24097730
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Soluble Factors from Tumor-Activated Mesenchymal Stromal Cells Confer Platinum Chemoresistance to Ovarian Cancer Cells

Abstract: Ovarian cancer (OC) ranks as the second most common type of gynecological malignancy, has poor survival rates, and is frequently diagnosed at an advanced stage. Platinum-based chemotherapy, such as carboplatin, represents the standard-of-care for OC. However, toxicity and acquired resistance to therapy have proven challenging for the treatment of patients. Chemoresistance, a principal obstacle to durable response in OC patients, is attributed to alterations within the cancer cells, and it can also be mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 70 publications
2
13
0
Order By: Relevance
“…As previously reported, cellular and soluble TME compartments play a role in conferring platinum chemoresistance to OC cells (21) (22) (23). Those findings showed that direct co-culture of OC with MSC resulted in conferring chemoresistance to therapeutic drugs such as paclitaxel, colchicine, and platinum compounds, alongside blocking of ERK1/2 activation (21).…”
Section: Introductionsupporting
confidence: 56%
See 4 more Smart Citations
“…As previously reported, cellular and soluble TME compartments play a role in conferring platinum chemoresistance to OC cells (21) (22) (23). Those findings showed that direct co-culture of OC with MSC resulted in conferring chemoresistance to therapeutic drugs such as paclitaxel, colchicine, and platinum compounds, alongside blocking of ERK1/2 activation (21).…”
Section: Introductionsupporting
confidence: 56%
“…This study is a follow-up to our earlier research that showed how a TME component promotes OC chemoresistance (23). Here, we carried out ex vivo assays to track the capacity of malignant ascites derived from OC patients to promote chemoresistance in OC cells.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations